(untitled) (Academicia Review-A Multidisciplinary Online Journal, 2026)
This article extensively covers the impact of proper nutrition on the human body, the principles of rational nutrition, the biological significance of nutrients, the consequences of poor nutrition, and its role in shaping a healthy lifestyle. Furthermore, from the perspective of modern dietetics and preventive medicine, the impact of nutrition on metabolic processes was analyzed based on scientific literature